Impact of Pressure Relief Holes on Core Coolability for a PWR during a Large-Break Loss-of-Coolant Accident with Core Blockage Using RELAP5-3D. (1st January 2016) - Vaghetto, Rodolfo; Crook, Timothy; Vanni, Alessandro; Hassan, Yassin A.
Abstract: During a loss-of-coolant accident (LOCA), fibrous debris and other particles generated by the jet impingement may be transported to the sump, accumulate, or even penetrate through the strainers, reaching the reactor core. Pressure relief holes and other plant-specific features may provide alternative paths to the coolant under debris-generated core blockage scenarios and can play a major role in core coolability. A typical four-loop pressurized water reactor was modeled using RELAP5-3D to simulate the reactor system response during large-break LOCA scenarios under hypothetical full core blockage conditions. Pressure relief holes were included in the input model to study the effects of these alternative flow paths on the core coolability. The comparison of the simulation results obtained with two different models (with and without pressure relief holes) proved the effectiveness of these alternative flow paths in providing sufficient flow to the core to remove the decay heat during the long-term cooling phase, maintaining the cladding temperature sufficiently below the safety limits at any time after the core blockage occurred. The results presented in this paper not only confirmed the importance of including specific geometric features of the reactor system (generally neglected) when simulating core blockage scenarios but also provided evidence that even under certain extreme core blockage conditions, core coolability may still be guaranteed.